Molecular Detection of Mycoplasma Hominis in Vaginal Swabs from Women with Urogenital Symptoms - Ali Habeeb, Rajaa (Journal La Lifesci, 2025)
Bacterial infections are a common cause of urogenital symptoms in women of reproductive age, which occurs usually as a result of imbalance in the normal vaginal flora and increase in anaerobic bacteria. Molecular investigation an involvement of M. hominis in urogenital infections of women, sequencing and submission of some positive study M. hominis isolates in the NCBI-GenBank database, and indicating the relationship between infection and some risk factors (age, previous medication, frequent compliance, and marital status). Totally, 191 diseased women with urogenital infections were attended to some private gynecology clinics and subjected to collection of vaginal swabs to be served for DNAs extraction. Targeting 16S rRNA gene, molecular examination was conducted using conventional PCR assay, and the, some positive samples were sequenced, submitted the NCBI-GenBank database, and analysed phylogenetically by the MEGA-11 software to indicate identity between the study and NCB-BLAST M. hominis isolates / strains. Molecular findings of PCR assay showed that 20.42% of study samples were positive to M. hominis. Sequencing data of 10 isolates revealed its identity to the global NCBI-BLAST Indian M. hominis isolate (ID: PP380133.1) at 99.06-99.77% and mutation / changes at 0.0001-0.00025%. Concerning the groups of risk factors, incidence of M. hominis infection was increased significantly in individuals aged 20-40 years than those aged <20 and >40 years, and non-medicated than frequent medication; however, insignificant variations were seen between the groups of frequent compliance and marital status.